Validity of a Content-Judged Instrument About the Implementation of Emotional Education Projects - Yunta-Ibarrondo, Miguel Ángel (2022)
Introduction. This study aims to design and validate the content of a questionnaire for teachers participating in emotional education projects at the levels of kindergarten, primary, and secondary education. The instrument aims to elicit teachers’ opinions on five factors that condition the implementation of emotional education projects. Method. Designing an instrument validation corresponding to the exploratory stage (content validity) of the construct factors, which affect the implementation in emotional education. The agreements of 11 judges determined content validity, and 4 existing instruments were adapted to design the questionnaire. The scale has five dimensions and is made up of 88 items. Results. The findings show that the questionnaire facilitates the organization of information into items by dimension and satisfies the criteria of sufficiency, clarity, coherence, and relevance. The instrument reaches a statistically significant inter-judge agreement, although the level of agreement is low. The modifications the judges indicated were incorporated. Conclusions. The evaluated instrument was finally composed of 86 items, of which 31 items were reformulated and 5 rejected. The level of measurement of the items included nominal measures (8 items) and 78 interval items. The findings show an adequate validity of the questionnaire, which proved to have a valid structure and content for the further validation of the metric properties of the instrument.